Synergistic Interaction Between Paired Combinations of Natural Antimicrobials Against Poultry-Borne Pathogens - Liu, Xiaoxia; Liu, Rui; Zhao, Ruting; Wang, Jishi; Cheng, Yongyou; Liu, Qian; Wang, Yanyun; Yang, Shuming (Frontiers in Microbiology, 2022)
Natural antimicrobials (NAM) are promising candidates for successful control of poultry-borne bacteria, carrying potent antimicrobial activity (AMA) against a wide range of multidrug-resistant pathogens. Individual activity of carvacrol, eugenol, trans-cinnamaldehyde, oregano, and thymol, along with the combined activity of paired compounds were examined via broth microdilution and checkerboard techniques. The characteristic interactions between the compounds were calculated using an improved method, based on combination index (CI) values. The bacteria examined herein were selected due to their known genetic resistance to at least one antibiotic. Our results indicated that thymol was most effective, exhibiting the lowest minimum inhibitory concentration (MIC) value against Salmonella pullorum, Escherichia coli, and Klebsiella pneumoniae, establishing the order of antimicrobial efficacy as: thymol > oregano > carvacrol > trans-cinnamaldehyde > eugenol. In the interaction study, the paired combination of carvacrol and thymol showed synergistic effects and was highly effective in reducing the antibiotic resistance of all the evaluated pathogens. Notably, all CI values were < 1.0 in evaluations of Salmonella pullorum, indicating the absence of antagonism between eugenol and thymol (or oregano). Considering Klebsiella pneumoniae, majority of CI values—barring a few concentration points—were smaller than 1.0, indicating a synergistic effect between eugenol and carvacrol (oregano or thymol), and trans-cinnamaldehyde and carvacrol. In the case of Escherichia coli, apart from some concentration points, some CI values were smaller than 1.0, demonstrating a synergistic effect between eugenol and carvacrol, and thymol and carvacrol (eugenol or oregano). Consequently, finding ways to minimize the unpleasant smell of these five components, would enable their application as feed additives. Moreover, the improved evaluation method of this study provides a precise and extensive means to assess the synergistic effects of NAM.